PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTY YANG TERDAFTAR DI BURSA EFEK INNDONESIA - Saputra Dharma, Eka; Panjaitan, Fery; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2022)
This research has been compiled and done by Eka Saputra Dharma, in the period February 2022 to July 2022 and is located in Pangkalpinang City, Bangka Belitung Islands Province, Indonesia. The research was conducted at the Agency; STIE_IBEK Pangkal Pinang Investment Gallery. This study aims to see the effect of profitability and liquidity on firm value in property sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period, using quantitative methods, while the sample in this study was 11 companies. The sampling technique used purposive sampling or sampling based on certain considerations and criteria. The results of the research data analysis show that: (1) Profitability has no positive and insignificant effect on firm value with a regression coefficient of -0.008 with a significant level of 0.105>0.05. (2) Liquidity has a positive and significant effect on firm value with a regression coefficient of 0.376 and a significant level of 0.084>0.05. (3) Profitability and liquidity have a positive and significant effect on firm value with a significant value of 0.112 with an R2 of 11.2%.